Three-phase three-level T-type grid-connected inverter with reduced number of switches - Altın, Necmi N.; Sefa, Ibrahim; Komurcugil, Hasan; Ozdemir, Saban S. (Institute of Electrical and Electronics Engineers Inc., 2018)
In this study, a three-phase three-level T-type neutral point clamped grid connected inverter with reduced number of switch is proposed for distributed generation systems. The proposed inverter topology has only two legs and totally eight semiconductor switches. Thus, advantageous multi-level inverter technology has been achieved with less number of semiconductor switches resulting in reduced circuit complexity. The proportional-resonant controller in stationary reference frame is designed to control the proposed inverter, thus fast dynamic response and good reference tracking ability is obtained with zero steady-state error. The feasibility and correct operation of the proposed system is validated through MATLAB/Simulink simulation studies. The obtained results show that proposed three-phase three-level T-type inverter exhibits comparable performance with the conventional T-type inverters. Furthermore, total harmonic distortion level of the output current is computed as 2.07%, which is in accordance with the limits specified by the international standards such as IEC61727 and IEEE1547. © 2018 IEEE.
6th International Istanbul Smart Grids and Cities Congress and Fair, ICSG 2018 -- 2018-04-25 through 2018-04-26 -- Istanbul -- 137884
Keywords: grid interactive; PR controller; reduced number of switches; T-type; three-level inverter; two-leg inverter